Primary knee arthroplasty for osteoarthritis restores patients' health-related quality of life to normal population levels: a propensity score matched study. (15th March 2023) - Yapp, Liam Z.; Scott, Chloe E. H.; MacDonald, Deborah J.; Howie, Colin R.; Simpson, A. Hamish R. W.; Clement, Nick D.
Abstract : Aims: This study investigates whether primary knee arthroplasty (KA) restores health-related quality of life (HRQoL) to levels expected in the general population. Methods: This retrospective case-control study compared HRQoL data from two sources: patients undergoing primary KA in a university-teaching hospital (2013 to 2019), and the Health Survey for England (HSE; 2010 to 2012). Patient-level data from the HSE were used to represent the general population. Propensity score matching was used to balance covariates and facilitate group comparisons. A propensity score was estimated using logistic regression based upon the covariates sex, age, and BMI. Two matched cohorts with 3, 029 patients each were obtained for the adjusted analyses (median age 70.3 (interquartile range (IQR) 64 to 77); number of female patients 3, 233 (53.4%); median BMI 29.7 kg/m 2 (IQR 26.5 to 33.7)). HRQoL was measured using the three-level version of the EuroQol five-dimension questionnaire (EQ-5D-3L), and summarized using the Index and EuroQol visual analogue scale (EQ-VAS) scores. Results: Patients awaiting KA had significantly lower EQ-5D-3L Index scores than the general population (median 0.620 (IQR 0.16 to 0.69) vs median 0.796 (IQR 0.69 to 1.00); p < 0.001). By one year postoperatively, the median EQ-5D-3L Index score improved significantly in the KA cohort (mean change 0.32 (SD 0.33); p < 0.001), and demonstrated no clinically relevant differences when compared to the general population (median 0.796 (IQR 0.69 to 1.00) vs median 0.796 (IQR 0.69 to 1.00)). Compared to the general population cohort, the postoperative EQ-VAS was significantly higher in the KA cohort (p < 0.001). Subgroup comparisons demonstrated that older age groups had statistically better EQ-VAS scores than matched peers in the general population. Conclusion: Patients awaiting KA for osteoarthritis had significantly poorer HRQoL than the general population. However, within one year of surgery, primary KA restored HRQoL to levels expected for the patient's age-, BMI-, and sex-matched peers. Cite this article: Bone Joint J 2023;105-B(4):365–372.